Homeostasis of the membrane proton permeability in Bacillus subtilis grown at different temperatures - van de Vossenberg, Jack L. C. M. (1999)
Bacillus subtilis was grown at its growth temperature limits and at various temperatures in between the lower and upper growth temperature boundary. Liposomes were made of the extracted membrane lipids derived from these cells. The headgroup composition of the cytoplasmic membrane lipids did not differ significantly at the lower (13°C) and upper (50°C) temperature boundary. The averaged lipid acyl chain length, degree of saturation, and ratio of iso- and anteiso-branched fatty acids increased with the temperature. At the temperature of growth, the membranes were in a liquid-crystalline phase, but liposomes derived from cells grown at 13°C were almost threefold more viscous than those derived from 50°C grown cells. The temperature dependence of the proton permeability of the liposomes was determined using the acid-pulse method with monitoring of the outside pH with the fluorescent probe pyranine. The proton permeability of each liposome preparation increased with the temperature. However, the proton permeability of the liposomes at the growth temperature of the cells from which the lipids were derived was almost constant. These data indicate that the growth temperature dependent variation in lipid acyl chain composition permits maintenance of the proton permeability of the cytoplasmic membrane. This [`]homeo-proton permeability adaptation' precludes futile cycling of protons at higher growth temperatures and allows cells to sustain the proton motive force as a driving force for essential energy transducing processes.